Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1021/jf025781x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Cancer Cells by Bilberry (Vaccinium myrtillus) and the Anthocyanins

Abstract: Among ethanol extracts of 10 edible berries, bilberry extract was found to be the most effective at inhibiting the growth of HL60 human leukemia cells and HCT116 human colon carcinoma cells in vitro. Bilberry extract induced apoptotic cell bodies and nucleosomal DNA fragmentation in HL60 cells. The proportion of apoptotic cells induced by bilberry extract in HCT116 was much lower than that in HL60 cells, and DNA fragmentation was not induced in the former. Of the extracts tested, that from bilberry contained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
244
3
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(274 citation statements)
references
References 30 publications
12
244
3
11
Order By: Relevance
“…In addition to vitamin A derivatives, there are many additional chemopreventive compounds that have elicited a variety of cancer preventing effects including induction of apoptosis, stimulation of differentiation and suppression of cell proliferation in both in-vitro and in-vivo models (25)(26)(27)(28). Relevant to this current study, compounds which provide natural colors to fruits and vegetables such as the anthocyanins, have been shown to demonstrate a wealth of chemopreventive properties (15,(27)(28)(29)(30). While anthocyanins represent the primary flavinoids in FBR, black raspberries also contain additional chemopreventive compounds including ferulic acid, coumaric acid, quercetin, and phtyosterols.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to vitamin A derivatives, there are many additional chemopreventive compounds that have elicited a variety of cancer preventing effects including induction of apoptosis, stimulation of differentiation and suppression of cell proliferation in both in-vitro and in-vivo models (25)(26)(27)(28). Relevant to this current study, compounds which provide natural colors to fruits and vegetables such as the anthocyanins, have been shown to demonstrate a wealth of chemopreventive properties (15,(27)(28)(29)(30). While anthocyanins represent the primary flavinoids in FBR, black raspberries also contain additional chemopreventive compounds including ferulic acid, coumaric acid, quercetin, and phtyosterols.…”
Section: Discussionmentioning
confidence: 92%
“…La actividad antioxidante es dependiente de la concentración del extracto [21,36]. La mejor respuesta obtenida, teniendo en cuenta los disolventes aplicados, es una concentración próxima a 0,04 g/mL para la mayor parte de las pulpas, exceptuando la pulpa de acerola con la que se obtiene una concentración de 0,004 g/mL.…”
Section: -Actividad Antioxidanteunclassified
“…El consumo de frutos y verduras esta asociado al bajo riesgo de incidencias y mortalidad de cáncer [7], y a menores índices de mortalidad por enfermedad coronaria [18,22], según se desprende de diversos estudios epidemiológicos. Los fenoles, especialmente los flavonoides [16] y los antocianos [9,16,24,31], muestran una gran capacidad para captar radicales libres causantes del estrés oxidativo, atribuyéndoseles a su vez un efecto beneficioso en la prevención de enfermedades tales como: cardiovasculares, circulatorias, cancerígenas y neurológicas [20,21,26,44,48,52]. Poseen actividades anti-inflamatoria, antialérgica, antitrombótica, antimicrobiana y antineoplá-sica [34,40,41,43].…”
Section: Introductionunclassified
“…In this study, the pigments found in purple yams from the Philippines (D. alata) were isolated and evaluated in terms of antioxidant activity. Four new acylated anthocyanins (1)(2)(3)(4) were isolated from the MeOH extracts of purple yam, which were subsequently determined to be cyanidin (1, 2, and 4) and peonidin (3) type compounds, along with four known anthocyanins (5)(6)(7)(8). The structures of 1-4 were determined by spectroscopic methods, including NMR and MS analyses.…”
mentioning
confidence: 99%